Awareness, Knowledge and Practices of Contraceptive Methods among Married Males of Slums of Phulwarisharif block of Patna District, Bihar - Shekhar, Raj; Bhar, Ditipriya; Singh, Chandramani (Indian Journal of Community Health, 2019)
Background: Even though India was the first country to launch family planning programme, population growth rate of India is still higher. Males are often the dominant decision makers of the family. Many studies regarding contraception has been done on females but the same is lacking on males. Aims & Objectives: The aim was to assess the level of awareness and practices about the contraceptive methods and factors associated with awareness and use among the married males in slums of Phulwarisharif block of Patna. Material & Methods: A cross-sectional study was conducted among 212 married males aged 18 to 60 years over a period of 3 months in slums of Phulwarisharif, Patna. Data were collected by interview of study subjects using predesigned and pretested questionnaire. Descriptive statistics and chi-square test were applied using SPSS software. Results: Among 212 married males 91.5 % have heard of at least one contraceptive method, while only 42.45% have ever used any contraceptive method. The major source of knowledge among 194 aware participants were friends and family members (78.9%). Age, duration of marriage, number of children and position in the family were associated with level of awareness. Conclusion: Despite of high awareness about contraceptives low utilization and limited knowledge was observed among the married male participants.